Cravo, rosa e flor de laranjeira : religiosidade, protagonismo feminino e negritude na Lavagem do Rosário em Cuiabá - Costa, Evilaine Silva da (2022)
This research ethnographed the possible intertwinings of the Lavagem das Escadarias de São Benedito in Cuiabá/MT, in the year 2019, considering that festive practices occupy a space of meaning within social dynamics. The study was also motivated by the objective of understan-ding how the washing of stairs can become a tool for occupying public spaces, renewing and affirming identities, redefining social actors. The field research took place in the last three days of preparation for the party: musicians' rehearsal, Ossain's ritual and the washing of the stairs. Armed with a camera, I sought a participant observation inspired by Favret-Saada, experien-cing the three stages and allowing the profile of a researcher to merge with that of a daughter of saint and vice versa, in an Anthropology immersed in life (Tim Ingold) . As a result, the dissertation points out some plexuses that develop in this party, making clear the multiplicity of meanings attributed to it. Therefore, Lavagem das Escadas de São Benedito embodies the concept of parliament of threads theorized by Ingold, by establishing meanings that include religious intolerance, female protagonism and blackness.